Diagnosis and treatment of asthma in athletes - Backer, V. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Asthma is frequently found among elite athletes performing endurance sports such as swimming, rowing and cross-country skiing. Asthma is characterised by respiratory symptoms during both rest and exercise, airway inflammation as well as AHR to multiple agents. Although these athletes often report symptoms while exercising, they seldom have symptoms at rest. Shortness of breath during exercise could be caused by asthma, but other conditions and diseases might induce exercise-induced respiratory symptoms, e.g. low physical fitness, laryngeal disorders, hyperventilation syndrome, and cardiac illnesses too. Although laryngeal disorders induce inspiratory shortness of breath, often during exercise, these disorders are frequently misclassified as asthma in elite athletes. Moreover, compared with non-athletic, asthmatic individuals, elite athletes have been shown to have a different distribution of airway inflammation and unequal response to bronchial provocative test. Elite athletes should undergo comprehensive assessment to confirm an asthma diagnosis and determine its degree of severity. Treatment should be as for any other asthmatic individual, including the use of beta2-agonist, inhaled steroid and leukotrien-antagonist, due the asthma severity classified in the guidelines. It should, however, be noted that daily use of betaagonists could expose elite athletes to the risk of developing tolerance towards these drugs. Use of beta2-agonist should be replaced with daily inhaled corticosteroid treatment, the most important treatment of exercise-induced asthma. All treating physicians should be aware of the doping aspects. Systemic beta2-agonist intake is strictly prohibited, whereas inhaled treatment is allowed in therapeutic doses when asthma is documented and dispensation has been granted when needed.